Особливості канадсько-китайських двосторонніх відносин - Білоус, Ольга Вікторівна (ЧНУ, 2021)
This master's thesis is presented for defense in the specialty "International Relations" at the Yuri Fedkovych National University of Chernivtsi
Магістерська робота
Keywords: Міжнародні відносини, канадсько-китайські відносини.